Analisis Peran Orang Tua dalam Pengembangan Ekstrakurikuler Sepak Bola - Lubis, Ade Evriansyah; Juliantine, Tite; Ma'mun, Amung; Sucipto, Sucipto (Jurnal Sporta Saintika, 2026)
The development of students’ non-academic potential through soccer extracurricular activities at the junior high school level is often hindered by limited internal school resources; therefore, a systematic approach that involves active parental support is needed to successfully foster students’ interests and talents. This study aims to comprehensively analyse the impact of various forms of parental support on the sustainability of soccer extracurricular programs at the junior high school level in Pekanbaru City. This study employs a qualitative approach using an Intrinsic Case Study design at three junior high schools (SMP Negeri 1 Pekanbaru, SMP Negeri 5 Pekanbaru, and SMP Negeri 10 Pekanbaru). Data were collected through triangulation (observation, interviews, and documentation) from parents, students, and coaches. The results indicate that parental support is vital and multidimensional, encompassing financial, moral, and logistical factors. This multifaceted support collectively has a significant impact on improving the quality of the development program. The conclusion affirms that parental support is a determining factor and catalyst for the success of a soccer extracurricular program. The implications of this study recommend establishing a structured parent-school partnership model to more comprehensively optimize the development of students’ interests and talents.